Schmidt Reaction of E-3-Benzylidenechromanones and E-3-Benzylidenethiochromanones - Tapas K. Mandal; Rammohan Pal; Rina Mondal; Sankar P. Dey; Asok K. Mallik (Journal of Chemistry)
On treatment with NaN3/c. H2SO4-HOAc or NaN3/TFA, E-3-benzylidenechromanones are mostly converted to E-β-aminobenzylidenechromanones while E-3-benzylidenethiochromanones are converted to 3-benzoylthiochromones. A structurally new type of product has been isolated for the reaction of E-3-benzylidene-4′-methoxychromanone with NaN3/TFA. Mechanistic paths have been suggested for formation of the products.